GELSTATS: A Computer Program for Population Genetics Analyses Using VNTR Multilocus Probe Data. (December 1996) - Rogstad, Steven H.; Pelikan, Stephan
GELSTATS, a computer program for population genetics analyses utilizing genetic markers revealed with variable number tandem repeat (VNTR) multilocus probes, is described and made available (both as C++ source code and as an executable DOS program). The program calculates several population genetics parameters, including: (i) individual and population band numbers; (ii) population bands exhibiting complete linkage (redundant examples of such bands can be removed in subsequent analyses); (iii) similarity (fraction of bands shared) between individuals and average similarity within and between designated groups; (iv) estimated probability that two individuals chosen at random will have identical band profiles; (v) heterozygosity estimates for designated groups; and (vi) Fst estimates. Nonparametric permutation methods are used to assess the significance of differences in both within- and between-group similarity. A jackknife test for heterozygosity differences between groups is also computed. Examples of GELSTATS analyses illustrate some features of the program.